Kelimpahan, Keanekaragaman, dan Pertumbuhan Alami Bintang Laut (Asteroidea) di Perairan Pantai Semawang dan Pantai Samuh, Bali - Ni Wayan Ernawati; I Wayan Arthana; Ni Made Ernawati (Current Trends in Aquatic Science, 2019)
Semawang beach and Samuh beach are located in the area of Sanur and ITDC Nusa Dua, Bali. This study aims to find out abundance, diversity, domination, natural growth of starfish, and to know the physical and chemical conditions of waters. The method used was descriptive quantitative method. The highest total abundance in sub station 1 was 0,0045 ind/m2 (Semawang beach), diversity index ranged from 0,86 to 1,06 and the dominance index ranged from 0,45 to 0,5. The highest total abundance in sub station 1 was 0,118 ind/m2 (Samuh beach), diversity index ranged from 1,32 to 1,92 and dominance index ranged from 0,21-0,4. The long range of arms (R), radius of disc (r), and weight (W) of the starfish found on Semawang beach and the Samuh beach was R: 5,9-13,6 cm, r: 0,9-7,8 cm, W: 15,6-1896,6 gr, and R: 3,6-11,6 cm, r: 0,5-7,9 cm, W: 6,3-1835,9 gr. The equation of arms length relation and weight and the relation of radius of disc and weight with the highest R2 value at Semawang Beach is found in the Pentaster obtusatus species W = 0,1738L2,8214 and 70% W = 11,9780L1,7876. The equation of arms length relation and weight and the relation of radius of disc and weight with the highest R2 value at Samuh beach is found in species Linckia guildingi W = 2,9166L0,6170 and W = 9,2138L0,5169. The measurement result water quality parameters in Semawang beach waters ranges from 29-30°C (temperature), 5,5-5,7mg/L (DO), 30,5-31,5 ppt (salinity), and 8,2-8,5 (pH), while in Samuh beach waters of ranges 28-28,5°C (temperature), 5,5 mg/L (DO), 30-30,8 ppt (salinity), and 7,7 (pH).